2011
DOI: 10.1128/aac.00542-11
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Vancomycin Activity against Biofilms by Using Ultrasound-Targeted Microbubble Destruction

Abstract: Treating biofilm infections on implanted medical devices is formidable, even with extensive antibiotic therapy. The aim of this study was to investigate whether ultrasound (US)-targeted microbubble (MB) destruction (UTMD) could enhance vancomycin activity against Staphylococcus epidermidis RP62A biofilms. Twelve-hour biofilms were treated with vancomycin combined with UTMD. The vancomycin and MB (SonoVue) were used at concentrations of 100 g/ml and 30% (vol/vol), respectively, in studies in vitro. After US exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 35 publications
2
83
1
Order By: Relevance
“…63 For example, US (0.08 MHz) targeted microbubble destruction of biofilm in an in vivo rabbit model enhanced the effects of vancomycin. 64 Similarly, biofilm growth in ciprofloxacin-loaded hydrogels with US induced (43 kHz ultrasonic bath for 20 minutes daily) was significantly lower compared controls. 65 Clearly, augmenting antibiotic treatment with ultrasound is a promising device combination for drug delivery to counter biofilms.…”
Section: Enhancement Of Antimicrobial Transport Using Ultrasoundmentioning
confidence: 99%
“…63 For example, US (0.08 MHz) targeted microbubble destruction of biofilm in an in vivo rabbit model enhanced the effects of vancomycin. 64 Similarly, biofilm growth in ciprofloxacin-loaded hydrogels with US induced (43 kHz ultrasonic bath for 20 minutes daily) was significantly lower compared controls. 65 Clearly, augmenting antibiotic treatment with ultrasound is a promising device combination for drug delivery to counter biofilms.…”
Section: Enhancement Of Antimicrobial Transport Using Ultrasoundmentioning
confidence: 99%
“…10,12,13 It has been recognized that MBs can present as cavitation nuclei to lower the cavitation threshold, thereby significantly facilitating transient cavitation which may generate shock waves and microjets. 31 Under such violent physical stress, high-density surfaces (eg, bacterial biofilm) become loose with emerging micropores and craters, allowing antibiotics to penetrate through the weakened matrix barrier and increase antibiotic concentration therein.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent studies have found that the cavitation-induced bactericidal effects against biofilms are based upon the cavitationally enhanced antibiotic activity within biofilms and the restored susceptibility of biofilmencapsulated cells to antibiotic action. [10][11][12][13] These effects are of high relevance to the mechanical destruction of biofilm barriers (ie, extracellular matrix), thereby promoting greater penetration of antibiotics surrounding the biofilms into the sessile bacterial community. In the setting of residual matrix scaffold, dormant cells in the deeper layer may recover metabolic activity.…”
mentioning
confidence: 99%
“…The biofilm-forming ability of S. epidermidis strains in vivo was determined by using a New Zealand rabbit subcutaneous foreign body infection model as described by He et al with minor modifications (33). Disks were cut from polyethylene 96-well plates (8-mm diameter, 1-mm thickness, with a 2-mm projecting rim or chimb), sterilized with 75% ethanol, washed with sterile distilled water, and then disinfected by using UV light.…”
Section: Methodsmentioning
confidence: 99%
“…The biofilms were scraped from the disks, and the viable bacteria were determined by CFU counting as previously described (16,33). Five independent experiments were carried out.…”
Section: Methodsmentioning
confidence: 99%